Experimentation in the cosmic laboratory. - Leconte-Chevillard, Gauvain (Studies in History & Philosophy of Science Part A, 2021)
It might seem impossible to apply Ian Hacking's experimental argument for scientific realism to astrophysical objects; indeed Hacking himself expressed scepticism about extragalactic entities. Such astrophysical antirealism has been the subject of intense debate and is usually seen as an undesired consequence of experimental realism. In this paper, I claim that it is possible to recast the experimental argument by reference to James Woodward's non-anthropocentric account of experimentation so as to apply it to astrophysical entities, such as gravitational lenses. I also argue that this new formulation of the experimental argument solves several problems with Hacking's original version.